2006
DOI: 10.1021/jp064686e
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Controlled Brønsted Acidity on a Zeotypic Mesoporous Chromium(III) Carboxylate by Grafting Water and Alcohol Molecules

Abstract: This paper reports a new way of modulating the strength of the Brønsted acid sites of a porous solid. Our approach consists of the grafting of various polar molecules (H 2 O, CD 3 OH, CF 3 CH 2 OH, and (CF 3 ) 2 CHOH) on MIL-100(Cr), a mesoporous crystallized chromium carboxylate with accessible unsaturated metal sites. We demonstrate, using infrared spectroscopy, that all these compounds do coordinate on the coordinatively unsaturated Cr 3+ sites. This generates controlled Brønsted acid sites whose strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 28 publications
3
98
0
1
Order By: Relevance
“…No products other than the isopulegols (2-5) were detected, while the selectivity for the isopulegol diastereomer (2) with respect to the other three diastereomers (3)(4)(5) As mentioned above, the most likely active sites in Cr 3+ -MIL-101 for the citronellal isomerization are coordinatively unsaturated Cr 3+ sites, created upon removal of the apical H 2 O ligand. Nevertheless, some studies [30][31][32] have revealed the presence of Bronsted type acidity in this class of solids, which could also contribute to the observed catalytic activity.…”
Section: Resultsmentioning
confidence: 97%
“…No products other than the isopulegols (2-5) were detected, while the selectivity for the isopulegol diastereomer (2) with respect to the other three diastereomers (3)(4)(5) As mentioned above, the most likely active sites in Cr 3+ -MIL-101 for the citronellal isomerization are coordinatively unsaturated Cr 3+ sites, created upon removal of the apical H 2 O ligand. Nevertheless, some studies [30][31][32] have revealed the presence of Bronsted type acidity in this class of solids, which could also contribute to the observed catalytic activity.…”
Section: Resultsmentioning
confidence: 97%
“…The change of the distribution of acid sites in MIL-100 with different degrees of hydration was semiquantitatively monitored. 84,87 The introduction of Brønsted acidity and an increase of Lewis acid sites in CF 3 COOH-or HClO 4 -treated MIL-100 were also studied using this method. 117 Although not as commonly used as CO, acetonitrile, also a small molecule with low basicity (pK b = 24), shows great potential for utility in determining strong Brønsted acid sites in MOFs.…”
Section: Vibrational Spectroscopy Methodsmentioning
confidence: 99%
“…A series of alcohols (methanol, trifluoroethanol, and hexafluoropropan-2-ol) with different pK a values have been introduced to bind to the coordinatively unsaturated Cr(III) sites in MIL-100, and the Brønsted acidity of resulting complexes was measured and compared in the same way that was followed for the water complex. 87 Alcohol-complexed MIL-100 was prepared by first activating the MOF at 473 K to fully remove the adsorbed water molecules and expose the open chromium sites, followed by introduction of alcohol vapor to form the complex. Similar to the water case, due to the coordination, the hydroxyl groups of the coordinated alcohol are more acidic, as previously shown on BF 3 −alcohol complexes in solution.…”
Section: Ligated Brønsted Acid Groupsmentioning
confidence: 99%
“…[80] ) shows Cr-OH Brønsted sites of medium acidity and several types of Lewis centers. [78,81] In our group, we have tested 1D MOF materials (rod-shape structure) with structurally well-identified hydroxy centers, namely [Ga(OH)(bdc)]…”
Section: Brønsted Acid Catalysismentioning
confidence: 99%